The experience of transition preparation for children and adolescents with mental disorders in China: a qualitative study - Miao, Yingying; Li, Juan; Wang, Jihong; Zhou, Xiaohuan; Li, Xin; Zhang, Yi; Xu, Hui (Frontiers in Psychology, 2025)
BackgroundAdolescence represents a critical transitional phase from pediatric to adult healthcare, during which young individuals with mental disorders encounter unique challenges; however, research on their transition experiences, particularly in non-English-speaking contexts such as China, remains limited.ObjectivesThis study aimed to explore the transition preparation experiences of adolescents with mental disorders in China as they move from pediatric to adult healthcare.MethodsQualitative semi-structured interviews were conducted with 15 children and adolescents diagnosed with mental disorders in China, and the data were analyzed using interpretive phenomenological analysis.FindingsThe study identified five primary themes related to the transition experiences of children and adolescents with mental disorders: (1) a discrepancy between transitional awareness and action; (2) gaps in transitional care throughout the healthcare transition process; (3) multidimensional needs within transitional care; (4) a contradiction between desire for self-management of illness and limited capacity; and (5) the dual attributes of family support, encompassing both enabling and constraining aspects.ConclusionThe study underscores the concerning transition readiness of adolescents with psychiatric disorders in China, marked by complex challenges and diverse needs, while highlighting the dual role of family support as both a motivating and obstructive force.